Antibiotic sensitivity of selected bacteria and microbiological quality of Lactobacillus-fed broiler meat in comparison with commercial broiler meat - Tan, Stephanie Yin Yi (2016)
The use of probiotics to replace antibiotics in poultry feed had been introduced in recent years. It is believed that probiotics may give the same overall health effect to livestock, without the undesirable development of antibiotic resistance to vital antibiotics. It is also believed that chickens fed with probiotics may have better overall microbiological quality. This study was performed to evaluate the Standard Plate Count (SPC), Coliform Plate Count (CPC) and antibiotic sensitivity of selected bacteria of Lactobacillus-fed broiler meat, and to compare them with those of commercial broiler meat. Twenty Lactobacillus-fed broiler meat and twenty-five commercial broiler meat were purchased from seven retail outlets within Selangor and Kuala Lumpur. Bacterial isolation of Salmonella sp., Escherichia coli and Staphylococcus aureus were performed on the meat samples. Four (20%) of the Lactobacillus-fed broiler meat samples were found to be positive for Salmonella sp.; 11 (55%) samples were positive for E. coli, and only one sample (5%) was positive for Staphylococcus aureus. For commercial broiler meat, one sample (4%) was positive for Salmonella sp.; 10 samples (40%) were positive for E. coli, and one sample (4%) was positive for Staphylococcus aureus. The difference in the prevalence of all three bacteria between the commercial and Lactobacillus-fed chickens was not significantly different. All isolates were subjected to antibiotic sensitivity test. For Salmonella sp., all isolates from both types of meat were found to be resistant to ceftriaxone and oxytetracycline. E. coli from both types of chicken were resistant to ceftriaxone, ampicillin, streptomycin and oxytetracycline, while resistance towards ciprofloxacin was observed in one isolate from commercial broiler meat. Staphylococcus aureus isolate from commercial broiler meat was resistant to oxytetracycline, while the isolate from Lactobacillus-fed broiler meat was susceptible to all antibiotics. The antibiotic sensitivity of Salmonella sp., E. coli and Staphylococcus aureus isolates between the two types of broiler meat were similar, with the exception to ampicillin sensitivity of E. coli that was significantly lower from commercial broiler meat, as compared to isolates from Lactobacillus-fed broiler meat. The mean SPC in Lactobacillus-fed broiler meat and commercial broiler meat were 17 x 104 and 44 x 104 cfu per gram of chicken meat respectively. The mean CPC were 23 x 103 and 30 x 103 cfu per gram of meat in Lactobacillus fed broiler meat and commercial broiler meat respectively. SPC of Lactobacillus-fed broiler meat was significantly lower than that of commercial broiler meat (P<0.05). However, the difference in CPC between the two types of broiler meat was not significant (P>0.05). This study suggests little difference in the microbiological quality of commercial and more expensive Lactobacillus-fed broiler meat.